Inferentialism-Based Mathematics Learning Model To Improve Students' Mathematical Reasoning Abilities - Simanungkalit, Rick Hunter; Angin, Renita Br Perangin; Mayasari, Dian; Junarti, Junarti; Ishak, Hasriani; Saragih, Ewin Handoco (STABN RADEN WIJAYA WONOGIRI, 2020)
The purpose of this study is to develop a valid, practical, and effective inferentialism-based learning model so that it is suitable for improving the mathematical reasoning abilities of junior high school students. The inferentialism-based learning model has a syntax consisting of 6 (six) phases, namely: 1) Apperception, 2) Responsive to Reasoning, 3) Space of Reasoning, 4) Scorekeeping, 5) Deduce, and 6) Closing. This development research uses a development model design adapted from Borg & Gall which consists of 3 (three) stages, namely: 1) Preliminary stage, 2) Design stage, and 3) Testing stage. The results of the study show: 1) The inferentialism-based learning model is valid, reviewed from a) content validity meets the needs and current knowledge, b) the developed learning tools are categorized as valid and can be used; 2) The inferentialism-based learning model is practical, reviewed from the implementation of the model in limited trials and extensive trials and 3) The inferentialism-based learning model is effective, reviewed from: a) its influence on students' mathematical reasoning abilities, and b) students' responses to the learning tools and learning processes that have been carried out are categorized as good.